Diversity of psammophyte communities on sand dunes and sandy soils of the northern Sahara desert - Marouane Azizi (Elsevier, 2021)
Background: Hot deserts contain several habitats where the diversity, structure and functional features of plant communities in certain habitats, such as sandy soils and dunes for instance, are little explored. Objectives: This study aimed to characterize the flora of sandy soils of the northern Algerian Sahara in order to determine the different plant functional traits and conservation aspects of the psammophytic communities for a sustainable management of phytogenetic resources. Methods: In seven sites representing different sandy habitats, spontaneous psammophytic communities were sampled using 70 floristic relevés ‘samples’ with an area of 100 m2 for each and 10 replicates per sampling site. In each sample, the number of individual of plant species was measured, then plant diversity and similarity was estimated per site. Several plant traits including lifeforms, morphological types, dispersal forms, Noy-Meir types and chorological categories were attributed for each plant species to characterize psammophyte communities. Results: Overall, plant diversity of Saharan sandy habitats was very low. The sampled sandy soils and dunes included 29 plant species classified into 27 genera and 18 families, with good representation of Poaceae and Brassicaceae. The arido-active species were dominant with 62.1% of the flora, which were mainly represented by perennial plants belonging to chamaephytes, hemicryptophytes and phanerophytes. Plants of sandy soils and dunes adopted various dispersal types, mainly dominated by anemochorous species. The chorological analysis revealed the existence of two endemic species to the Sahara Desert whereas the Mediterranean-Saharan-Arabian species were mostly represented by the Saharo-Arabian element which adapts well to environmental conditions of the Sahara. The assessment of plant abundances showed that the community of psammophytes contained three rare plants, one quite rare species and two fairly common plants in the flora of Algeria. Accordingly, sandy habitats require adequate management measures in order to preserve the biodiversity in Saharan environments. The number of plant species, genera and families significantly increased with the increase in vegetation cover on sand dunes. Conclusions: The results of this survey can represent a first floristic database providing good indicators on plant communities, habitat and environmental conditions of sandy soils and dunes of the Algerian Sahara.